A review of significant aspects contributing to curriculum development - Rajurkar, Savita; Chavan, Kalidas D.; Kachewar, Sushil G.; Giri, Purushottam A. (International Journal of Research in Medical Sciences, 2018)
Curriculum is an essentially signified foundation of an academic arena. The master key of the treasure curriculum is anchored in its development. The basic and progressive aspects are the prominent spectrums of curriculum in navigating the stakeholders. Empowerment of curriculum by augmenting its development has been a topic of ongoing discussion in the enrichment of the educational field. By reviewing selected past and present relevant articles, this review article is aimed to provoke and fortify insights for the due perfection, systematization, and standardization in the futuristic aspects towards curriculum development. This is a sincere effort to present the versatile role of the concept of curriculum development and validate its significant aspects by keeping the various stakeholders in mind. It is hoped that this article would help motivate elder and newer generations of curriculum developers, academicians and researchers for expounding the process, for recognizing the intrinsic and upcoming challenges in the field of curriculum development for recognizing needs to refresh, update technology and upgrade pedagogics, for standardizing curriculum at the global application and for instigating an urge to research various aspects of this topic to bring in the due change, advancement and standardization.